Diffusion‐prepared stimulated‐echo turbo spin echo (DPsti‐TSE): An eddy current‐insensitive sequence for three‐dimensional high‐resolution and undistorted diffusion‐weighted imaging. (13th March 2017) - Zhang, Qinwei; Coolen, Bram F.; Versluis, Maarten J.; Strijkers, Gustav J.; Nederveen, Aart J.
Abstract : In this study, we present a new three‐dimensional (3D), diffusion‐prepared turbo spin echo sequence based on a stimulated‐echo read‐out (DPsti‐TSE) enabling high‐resolution and undistorted diffusion‐weighted imaging (DWI). A dephasing gradient in the diffusion preparation module and rephasing gradients in the turbo spin echo module create stimulated echoes, which prevent signal loss caused by eddy currents. Near to perfect agreement of apparent diffusion coefficient (ADC) values between DPsti‐TSE and diffusion‐weighted echo planar imaging (DW‐EPI) was demonstrated in both phantom transient signal experiments and phantom imaging experiments. High‐resolution and undistorted DPsti‐TSE was demonstrated in vivo in prostate and carotid vessel wall. 3D whole‐prostate DWI was achieved with four b values in only 6 min. Undistorted ADC maps of the prostate peripheral zone were obtained at low and high imaging resolutions with no change in mean ADC values [(1.60 ± 0.10) × 10 −3 versus (1.60 ± 0.02) × 10 −3 mm 2 /s]. High‐resolution 3D DWI of the carotid vessel wall was achieved in 12 min, with consistent ADC values [(1.40 ± 0.23) × 10 −3 mm 2 /s] across different subjects, as well as slice locations through the imaging volume. This study shows that DPsti‐TSE can serve as a robust 3D diffusion‐weighted sequence and is an attractive alternative to the traditional two‐dimensional DW‐EPI approaches. Abstract : A new three‐dimensional, eddy current‐insensitive, diffusion‐prepared stimulated‐echo turbo spin echo (DPsti‐TSE) sequence was developed that enables high‐resolution and undistorted diffusion‐weighted imaging (DWI). Excellent agreement of apparent diffusion coefficient (ADC) values obtained by DPsti‐TSE and diffusion‐weighted echo planar imaging (DW‐EPI) was demonstrated in phantoms. High‐resolution undistorted diffusion‐weighted images of in vivo prostate and carotid vessel wall were obtained.